Solved
Last edited by Insignia21; Jul 1st 2009 at 06:14 AM.
Follow Math Help Forum on Facebook and Google+
Originally Posted by Insignia21 If f(x)=3x^2 -5 and g(x)=x-6 find (f+g)(-2) This is the same as saying evaluate $\displaystyle f\!\left(-2\right)+g\!\left(-2\right)$ Simply evaluate both of your functions at -2 and add the results together. Can you try to take it from here?
Originally Posted by Insignia21 If f(x)=3x^2 -5 and g(x)=x-6 find (f+g)(-2) Hello : coclusion :
Originally Posted by Insignia21 If f(x)=3x^2 -5 and g(x)=x-6 find (f+g)(-2) $\displaystyle (f + g)(x) = f(x) + g(x)$ $\displaystyle = 3x^2 - 5 + x - 6$ $\displaystyle = 3x^2 + x - 11$ $\displaystyle (f + g)(-2) = 3(-2)^2 - 2 - 11$ $\displaystyle = 12 - 13$ $\displaystyle = -1$
View Tag Cloud